The Rivalry of Retired Soldier in the 2019 Indonesian Election - Eko Cahyono; Kamila Suci Cahyani; Muhamad Alvin Fadillah; Yunita Dwi Alfiani (Social Impact Journal, 2022)
The role of retired TNI officers in Indonesian politics is very significant, especially during the New Order era, when they had considerable influence in political and electoral processes. Competition between retired officers can influence election results, as shown by the conflict between the "Red and White" and "Cendana" groups during the 1987 and 1992 elections. In general, however, retired TNI officers still supported the New Order government and did not significantly affect the election results. After the Reformation era, many military retirees entered the world of politics and government, but competition between them became a complex problem. The government and related institutions are trying to address this problem by promoting communication and cooperation among retired military officers and educating them about democratic values ​​and human rights. Many retired generals, such as Suharto, Susilo Bambang Yudhoyono, Wiranto, and Luhut Binsar Pandjaitan, have played important roles in Indonesian politics as politicians. However, their involvement in politics can lead to competition and conflict, especially since they are often divided into opposing camps in the political arena.